COMMUNITY PERCEPTION OF THE POTENTIAL ENVIRONMENTAL SERVICES AT ECO-EDUTOURISM TAPAK MANGROVE, SEMARANG CITY - Wahyu Kisworo (Yayasan Nusantara Hasana Berdikari, 2023)
Mangroves are a type of dicotyledonous plant that is easily found in coastal estuary areas with swampy or dense structures, with various benefits in ecological, biological, and economic aspects. Edu-Ecotourism Tapak Mangrove is one of the mangrove tourist areas in the city of Semarang. The purpose of this research was to determine the potential of Edu-Ecotourism Tapak Mangrove environmental services with community perceptions, including provision services, regulatory services, cultural services, and supporting services. Primary data collection methods are observation, questionnaires, and interviews. Secondary data includes journal literature, books, and related regulations. The analysis was carried out using a qualitative-descriptive approach. Results showed that the characteristics of the respondents were dominated by residents of Semarang City with an age range of >35 years, and an income above Rp.3,000,000. Eco-Edutourism Tapak Mangrove provides four types of environmental services, including provision services, regulatory services, cultural services, and supporting services. The potential for the provision of services is obtained from 11 types of mangrove plants at the location, along with the carbon absorption received. Potential regulatory services have an average respondent result of 91%. Potential regulatory services include the benefits of mangroves to withstand the onslaught of sea waves, maintain water quality, protect ponds from erosion, withstand strong winds, provide air purification, provide a sense of comfort to visitors, and prevent climate change. Cultural services include benefits for recreation (natural tourism and education), pond cultivation, work, and research. The potential for supporting services has an average respondent result of 98.7%. The potential supporting services in this park include the benefits of producing oxygen, improving the fertility of the mangrove ecosystem, and providing a habitat for flora and fauna.